2019
DOI: 10.3390/hydrology6030063
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Mitigation of Streamflow and Sediment Yield under Climate Change Conditions in Diyala River Basin, Iraq

Abstract: The impact of climate change on the streamflow and sediment yield in the Derbendkhan and Hemrin Watersheds is an important challenge facing the water resources of the Diyala River in Iraq. The Soil and Water Assessment Tool (SWAT) was used to project this impact on streamflow and sediment yield until year 2050 by applying five climate models for scenario A1B involving medium emissions. The models were calibrated and validated based on daily observed streamflow and sediment recorded for the periods from 1984 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…After the evaluation of developed model performance, it was learned that the range of NSE varied from 0.51 to 0.57 and 0.60 to 0.83 for daily and monthly scale, respectively. This range is quite similar or even better than the 0.69 to 0.75 (on a monthly scale) found by [34] for a Mediterranean agricultural watershed (2.07 km 2 ) in Spain, 0.73 (on a monthly scale) by AnnAGNPS found by [26] for a 289.3 km 2 watershed in Illinois, USA, 0.65 (on a monthly scale) by SWAT and 0.48 to 0.58 (on a monthly scale) by AnnAGNPS found by [36] for a Mediterranean watershed (506 km 2 ) in Southern Italy, 0.53 (on a daily scale) by SWAT found by [67] for a large 1110 km 2 agricultural watershed in southwest France, 0.67 to 0.84 (on a monthly scale; calibration phase) found by SWAT for a large 4000 km 2 watershed in the North Carolina coastal plain [68], and the 0.53 to 0.62 (on a daily scale) found by SWAT for two watersheds in a semiarid region of Iraq [69]. Even, if we look at the value of R 2 from our study, it ranged from 0.54 to 0.66 (daily) and 0.64 to 0.86 (monthly).…”
Section: Discussionmentioning
confidence: 88%
“…After the evaluation of developed model performance, it was learned that the range of NSE varied from 0.51 to 0.57 and 0.60 to 0.83 for daily and monthly scale, respectively. This range is quite similar or even better than the 0.69 to 0.75 (on a monthly scale) found by [34] for a Mediterranean agricultural watershed (2.07 km 2 ) in Spain, 0.73 (on a monthly scale) by AnnAGNPS found by [26] for a 289.3 km 2 watershed in Illinois, USA, 0.65 (on a monthly scale) by SWAT and 0.48 to 0.58 (on a monthly scale) by AnnAGNPS found by [36] for a Mediterranean watershed (506 km 2 ) in Southern Italy, 0.53 (on a daily scale) by SWAT found by [67] for a large 1110 km 2 agricultural watershed in southwest France, 0.67 to 0.84 (on a monthly scale; calibration phase) found by SWAT for a large 4000 km 2 watershed in the North Carolina coastal plain [68], and the 0.53 to 0.62 (on a daily scale) found by SWAT for two watersheds in a semiarid region of Iraq [69]. Even, if we look at the value of R 2 from our study, it ranged from 0.54 to 0.66 (daily) and 0.64 to 0.86 (monthly).…”
Section: Discussionmentioning
confidence: 88%
“…This data comprises two layers (0 to 30 cm and 30 to 100 cm depth) at a spatial scale of 1:5000000. The basin's response to rainfall events depends on the nature and conditions of the underlying soil [28]. The dataset was processed using ArcGIS 10.4 program.…”
Section: Soil Mapmentioning
confidence: 99%
“…Iraq is part of the arid and semi-arid region of the MER, and, in Iraq, about 98% of the agricultural, municipal, environmental and industrial water needs depend on the Euphrates and Tigris Rivers [17]. However, most previous works have reported that the water resources of both rivers will decline due to human activities in upstream countries and climate change effects [17][18][19]. On the other hand, the water demand is expected to increase due to increased evaporation, a decline in precipitation and rapid population growth [20,21].…”
Section: Introductionmentioning
confidence: 99%